Moral reasoning theory : between Kohlberg’s and al-Ghazali’s perspective - Fariza Md Sham; Yaqin, Ainul; Wachidah, Hajar Nurma (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study was to examine the moral theory in al-Ghazali's classic Islamic compared Kohlberg's theory of moral level. The method used is the document analysis method with references to al-Ghazali works 'Ihya' Ulum al-Din's and articles related to Kohlberg's theory. The results show that there are similarities in the theory of moral level developed by al-Ghazali with Kohlberg, although there are also have differences. The level of moral reasoning classified by Kohlberg are divided into three which are preconventional, conventional and post-conventional which have similarities to al- Ghazali's moral classifications of the `awam, the khawas, and the khawas al-khawas. The difference is that Kohlberg's moral level is purely cognitive in its focus on moral reasoning, whereas al-Ghazali's moral level is on moral reasoning as well as behaviour.